INTERPRETASI DAN IMPLEMENTASI WAHYU DALAM ISLAM - Hilman Nafian; Indo Santalia (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2022)
Al-Revelation (revelation) is the word masdar (infinitive). He points to two basic meanings: hidden and fast. Therefore, it is said "revelation is information hidden and fast specifically addressed to certain people without being known to others. However, sometimes it also means A-Muha, namely the understanding of isim maf'ul, the meaning of which is revealed, in the Qur'an revelation is repeated 78 times, namely in the form of a noun (isim) 6 times and in the form of a verb (fi). 'il) 72 times. The discussion of revelation in Islam is a universal discussion that is not limited by place and time. Revelation is a process of communication between Khaliq and His creatures, especially humans. This research uses the type of literature review research. The data sources of this research are articles, books, journals and so on. The analytical technique used is to examine, analyze, and draw conclusions. From this research, we can see that the notion of revelation is mentioned as Ilham Al-fitri li Al-Insan, inspiration in the form of instinct to animals, inspiration that is quick through signs, whispers of Satan to decorate the bad so that it looks beautiful in humans, what Allah conveys. to His angels in the form of an order to be done. Islam places revelation in a more dominant position over reason in the main commands, for example in matters of worship and events related to the orders of the Prophet Muhammad in his time.